Effect of grain size on mechanical properties and tribological behavior of size-tunable high entropy diboride ceramics obtained by two-step SPS sintering - Yao Yang; Jianqiang Bi; Linjing Qiao; Guandong Liang; Shuyong Liang; Shushuai Liu; Shaoyin Wang; Hongyu Gong; Zhao Qian; Jinwang Shi; Weiqiang Li (Journal of Advanced Ceramics)
High-entropy diboride (HEB) ceramics constitute a novel class of ultrahigh-temperature ceramics that are appealing for applications in extreme environments. The relative density and grain size play important roles in tailoring the mechanical properties and wear resistance of HEBs, affecting their applications, such as high-temperature structural parts and thermal protection systems. In this study, highly dense (HfZrTaVNb)B2 ceramics with size-tunable microstructures were successfully synthesized by spark plasma sintering combined with an ingenious two-step strategy. The effects of grain size on the mechanical properties and wear resistance of (HfZrTaVNb)B2 ceramics were comprehensively investigated. The results indicated that the smaller grain size led to higher hardness and fracture toughness, and the relationship between hardness and grain size fitted the Hall–Petch equation well. In particular, the sample featuring a grain size of 1.64 µm and 97.6% density had the highest hardness and fracture toughness, 26.7 GPa and 4.6 MPa·m1/2, respectively. Notably, it also demonstrated optimal wear resistance, displaying a minimal wear rate of only 2.53×10−6 mm3/(N·m) under a 20 N load. Microstructure analysis revealed that the primary wear mechanism observed in (HfZrTaVNb)B2 was oxidative wear under a 5 N load. Under a 10 N load, the wear mechanism comprised both oxidative and fracture wear. The wear mechanism became more complex and involved oxidation wear, fracture wear, abrasive wear, and fatigue wear at a 20 N load.